Artistry : a creative exploration of a time-treatured drawing technique. - Jover, Loui (Artistry., 2016)
Combining practical instruction, inspirational art, and photographs, Pen & Ink explores drawing techniques from using ballpoint pen to stippling portraits and adding watercolor washes.